The Effectiveness of Civil Servant Profession Zakat Management in Ensuring Legal Certainty: A Case Study of Indonesia's National Zakat Agency - Triana Nur Israyani; Sufirman Rahman; Z. Zainuddin (Golden Ratio of Law and Social Policy Review, 2025)
The management of professional zakat in Indonesia, particularly by the National Zakat Agency (BAZNAS) in Pangkep Regency, faces significant challenges. Despite a national zakat potential of IDR 327 trillion in 2024, actual collection is only about IDR 41 trillion. In Pangkep, the policy of zakat profession deductions for Civil Servants (ASN) based on the Regent Circular No. 49/IV/KESRA/2021 has faced resistance due to weak legal foundations, insufficient socialization, and a lack of transparency, resulting in low ASN trust in zakat management institutions. This study aims to assess the effectiveness of ASN zakat management by BAZNAS in ensuring legal certainty and to identify factors contributing to resistance. Using a descriptive qualitative approach with a juridical-empirical methodology, data were gathered through interviews, non-participant observations, documentation, and questionnaires. The results show a 6.05% decrease in zakat revenue from 2023–2024, indicating poor ASN participation due to perceived coercion and lack of transparency. The study highlights weak regulations, minimal ASN involvement in decision-making, and insufficient transparency in zakat fund reporting as major barriers. The findings suggest that strengthening the legal framework, implementing participatory socialization, improving digital reporting systems, and institutional reforms focused on transparency and fairness are necessary to ensure the effectiveness and legal certainty of zakat management in Pangkep.